2015
DOI: 10.5603/cj.a2015.0001
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency QRS analysis compared to conventional ST-segment analysis in patients with chest pain and normal ECG referred for exercise tolerance test

Abstract: Background: The novel analysis of high-frequency QRS components (HFQRS-analysis) has been proposed in patients with chest pain (CP) and normal electrocardiography (ECG) referred for exercise tolerance test (ex-ECG HFQRS (area: 0.655, ST-segment-analysis. (Cardiol J 2015; 22, 2: 141-149)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
3
2
0
3
Order By: Relevance
“…This is in line with a previous study by Conti et al, who found a similar prognostic value of HF-QRS in 337 patients undergoing exercise stress testing. 34 Particular strengths and limitations of the HF-QRS technology merit consideration. The potential of automated test interpretation in cardiology is well known 8,35 and automatically computed ECG markers with improved diagnostic accuracy that are simple, readily available and interpretable by a wide range of healthcare professionals are an unmet clinical need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a previous study by Conti et al, who found a similar prognostic value of HF-QRS in 337 patients undergoing exercise stress testing. 34 Particular strengths and limitations of the HF-QRS technology merit consideration. The potential of automated test interpretation in cardiology is well known 8,35 and automatically computed ECG markers with improved diagnostic accuracy that are simple, readily available and interpretable by a wide range of healthcare professionals are an unmet clinical need.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a previous study by Conti et al, who found a similar prognostic value of HF-QRS in 337 patients undergoing exercise stress testing. 34…”
Section: Discussionmentioning
confidence: 99%
“…Nghiên cứu lâm sàng do nhóm tác giả Conti và cộng sự [13] Nhồi máu cơ tim được chẩn đoán dựa trên chỉ số HFMI là tỷ lệ phần trăm giữa diện tích phần RAZ so với diện tích bên dưới đường bao của phức bộ HFQRS và có thể được tính bằng công thức sau:…”
Section: Mở đầUunclassified
“…Một bản ghi ECG được coi là thiếu máu cục bộ nếu phát hiện ít nhất 3 chuyển đạo thiếu máu cục bộ và đồng thời chỉ số HFMI được chẩn đoán trong ít nhất 5 chuyển đạo, hoặc giá trị chỉ số HFMI (được tính trung bình từ 6 chuyển đạo có chỉ số HFMI lớn nhất) có giá trị lớn hơn 9%. Hiệu suất của thuật toán đề xuất cũng được so sánh với kết quả được công bố trong 3 thử nhiệm lâm sàng (Toledo [10], Conti [13], Galante [14]). Cả 3 nghiên cứu lâm sàng đều chỉ ra được lợi ích của việc sử dụng tín hiệu ECG tần số cao trong quá trình chẩn đoán bệnh thiếu máu cơ tim.…”
Section: Mở đầUunclassified
See 1 more Smart Citation